Preparation method and application of solid waste-based geopolymer composite carbon dioxide adsorption and desorption material
The solid waste base polymer composite adsorbent material is prepared by combining slag with solid waste bottom ash or fly ash with water glass, sodium hydroxide and tetraethylene pentamine, and the equipment in the existing CO2 capture technology is solved The problems of high corrosion and regeneration requirements and low adsorption efficiency have achieved efficient and low-cost carbon dioxide adsorption and desorption effects, and have promoted the resource utilization of solid waste.
Patent Information
- Application Number
- CN202411537264.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-14
AI Technical Summary
The existing CO2 capture technology faces problems such as equipment corrosion, high regeneration requirements, low absorption efficiency and degradation. In addition, the amine functionalized adsorbent has poor amine volatility and dispersion during the preparation process, resulting in slow carbon dioxide adsorption rate and high energy consumption.
The preparation method of solid waste base polymer composite carbon dioxide absorption and desorption materials is adopted, and the reaction is prepared by mixing slag with garbage bottom ash or fly ash, combining water glass, sodium hydroxide and tetraethylene pentamine at room temperature and pressure. Materials with high adsorption properties are produced.
It realizes high-efficiency adsorption and low-energy consumption desorption of carbon dioxide after heating at room temperature and normal pressure, reduces production costs, and has high thermal stability of the material, is suitable for large-scale production, and realizes the resource utilization of solid waste.
Smart Images

Figure CN119303540A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon dioxide adsorption, and in particular to a preparation method and application of a solid waste-based polymer composite carbon dioxide adsorption and desorption material. Background Art
[0002] Post-combustion capture is regarded as an economical and feasible method for efficiently capturing CO2 gas in flue gas. At present, the processes for post-combustion CO2 capture include chemical solution absorption, physical adsorption, chemical adsorption and membrane separation. Among the many CO2 capture methods, the use of organic amine solution to absorb CO2 is the most widely used chemical absorption capture technology. The process involves the reaction of amine solution with CO2 in the flue gas pipeline to generate unstable carbamate. Under heating or reduced pressure conditions, carbamate will undergo reverse decomposition and release CO2, realizing the regeneration of the absorbent and achieving the goal of carbon capture and recycling. At present, this technology has been widely used in industrial projects with large fixed carbon emission sources. However, this technology is challenged by problems such as equipment corrosion, high regeneration requirements, low absorption efficiency and degradation.
[0003] To meet these challenges, the development of low-cost and efficient CO2 capture materials has become a hot topic in current research. At present, porous solid adsorbents including amine-functionalized adsorbents, zeolites and metal-organic framework compounds have been widely used for carbon dioxide capture. In particular, amine-functionalized adsorbents have high selectivity and water vapor resistance, and are suitable for various application scenarios involving humid and low-concentration carbon dioxide environments. Generally, amine-functionalized adsorbents use porous solid carriers to load organic amines on their surfaces, and achieve efficient CO2 capture through the interaction between amine molecules and CO2 molecules. Compared with the method of absorbing CO2 with amine solutions, this adsorbent combines the high affinity between organic amines and CO2 and the advantages of porous carriers, thereby achieving lower regeneration energy consumption and higher adsorption capacity. In the process of loading organic amines on solid carriers, physical impregnation is currently generally used. However, during the physical impregnation process, organic amines may evaporate or leach from the surface of the adsorbent, resulting in a decrease in adsorbent performance over time, and whether the amine can be evenly dispersed during the amine loading process also affects the adsorption capacity of the adsorbent; in order to improve the adsorption performance, it is necessary to optimize the impregnation conditions and the loading amount of amine, which may increase the complexity and cost of the process.
[0004] Previous studies have mainly focused on expanding the support mesopores (2-50nm) to increase the amine loading. However, due to the poor dispersion of amines in the support, aggregation often occurs, which greatly increases the diffusion resistance of carbon dioxide and leads to a slow carbon dioxide adsorption rate. In addition, these adsorbents usually require higher carbon dioxide desorption temperatures or higher pressure conditions, resulting in increased energy consumption and capture costs. Therefore, how to improve the preparation conditions of amine-functionalized adsorbents, reduce costs and achieve atmospheric pressure adsorption still needs to be studied. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method and application of a solid waste-based polymer composite carbon dioxide absorption and desorption material. The preparation method has a simple process, low cost, and a short time. The obtained material adsorbs carbon dioxide under normal temperature and pressure conditions and desorbs after heating, and can be used for large-scale production.
[0006] In order to solve the problems of the prior art, the technical solution adopted by the present invention is:
[0007] A method for preparing a solid waste-based polymer composite carbon dioxide adsorption-desorption material, wherein the solid waste-based polymer composite adsorption material has a carbon dioxide adsorption-desorption function, the solid waste is a solid waste mixture formed by mixing slag with garbage bottom ash or fly ash, and the preparation method comprises the following steps:
[0008] Step 1, weighing garbage bottom ash or fly ash, slag, water glass, sodium hydroxide, water and tetraethylene pentamine in parts by weight, mixing the garbage bottom ash or fly ash and slag in a mass ratio to obtain a solid waste mixture; mixing water glass, sodium hydroxide and water to obtain an alkaline activator;
[0009] Step 2, mixing the solid waste mixture, alkaline activator and tetraethylenepentamine, stirring evenly to obtain slurry, and curing at 20-35° C. to obtain a solid waste-based polymer composite adsorption material.
[0010] As an improvement, the stirring speed when mixing the solid waste mixture in step 1 is 200 rpm, and the stirring is for 2 minutes.
[0011] As an improvement, in step 1, the mass ratio of bottom ash or fly ash to slag in the solid waste is 9:1-1:9.
[0012] As an improvement, the particle size of the garbage bottom ash and slag in step 1 is 120 mesh.
[0013] As an improvement, the particle size of the fly ash in step 1 is less than 325 mesh.
[0014] As an improvement, the alkali content of the alkaline activator in step 2 is calculated as the mass percentage of Na2O in the solid waste mixture, the water glass modulus is 0.7-1.7, and the mass ratio of water to the solid waste mixture is 0.5-0.6:1.
[0015] As an improvement, in step 2, the loading amount of tetraethylenepentamine is 2.5wt%-10wt%.
[0016] As an improvement, in step 2, the stirring speed is 600 rpm, the stirring time is 20 minutes, and the standing time after stirring is 2 days.
[0017] The solid waste-based polymer composite adsorption material prepared by the above preparation method has a simple preparation process, is easy to operate, has low cost and high thermal stability.
[0018] The solid waste-based polymer composite adsorption material prepared by the above-mentioned preparation method is used for the adsorption and desorption of carbon dioxide. It adsorbs CO2 at room temperature with excellent adsorption performance, and desorbs CO2 after heating. It not only realizes the resource disposal of solid waste, but also can adsorb and store carbon dioxide, and can also desorb carbon dioxide to extinguish fire after fire occurs, and has good application prospects.
[0019] Beneficial Effects
[0020] Compared with the prior art, the preparation method and application of a solid waste-based polymer composite carbon dioxide adsorption and desorption material of the present invention have the following advantages:
[0021] (1) The reaction conditions are mild, the steps are short, the synthesis is carried out at room temperature and pressure, and the operation is simple; the reaction is synthesized in one step, the post-processing is convenient and simple, and no expensive catalyst is required.
[0022] (2) Using solid waste as raw materials can not only absorb and store carbon dioxide, but also recycle solid waste as a resource, which is of great significance for green environmental protection.
[0023] (3) The prepared solid waste-based polymer composite carbon dioxide adsorption and desorption material can start desorption at relatively low temperature under normal pressure;
[0024] (4) The organic amine selected in the present invention is tetraethylenepentamine. If polyethyleneimine is selected, it is not used because it is too viscous and not easily soluble in water, and the reaction is prone to unevenness during preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a CO2-TPD analysis curve of the solid waste-based polymer composite carbon dioxide absorption and desorption material with an alkali dosage of 14% prepared in Example 1 of the present invention.
[0026] Figure 2This is a CO2-TPD analysis curve of the solid waste-based polymer composite carbon dioxide absorption and desorption material with an alkali dosage of 16% prepared in Example 2 of the present invention.
[0027] Figure 3 This is a CO2-TPD analysis curve of the solid waste-based polymer composite carbon dioxide absorption and desorption material with an alkali dosage of 18% prepared in Example 3 of the present invention.
[0028] Figure 4 This is a CO2-TPD analysis curve of the solid waste-based polymer composite carbon dioxide absorption and desorption material with an alkali dosage of 20% prepared in Example 4 of the present invention.
[0029] Figure 5 This is a CO2-TPD analysis curve of the solid waste-based polymer composite carbon dioxide absorption and desorption material prepared in Example 5 of the present invention, in which the solid waste is fly ash and slag.
[0030] Figure 6 This is a bar chart of the CO2 adsorption capacity of the solid waste-based polymer composite carbon dioxide adsorption and desorption material prepared in Examples 1-5 of the present invention.
[0031] Figure 7 This is a physical picture of the solid waste-based polymer composite carbon dioxide absorption and desorption material in which the organic amine is polyethyleneimine, prepared in Comparative Example 1 of the present invention.
[0032] Figure 8 The present invention is a flow chart of a method for preparing a solid waste-based polymer composite carbon dioxide absorption and desorption material. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The experimental methods used in the following examples are conventional methods unless otherwise specified, and the materials, reagents, etc. used in the examples are commercially available unless otherwise specified. The reaction conditions embodied in the content of the invention of the present invention are all capable of achieving the reaction and obtaining the product of the expected effect. Due to space limitations, only some embodiments are listed below to further illustrate the advantages of the technical solution of the present invention.
[0035] The water glass in each embodiment of the present invention is sodium water glass, wherein the solid components are SiO2 and Na2O, and the mass fractions are 26.98% and 8.53% respectively.
[0036] Example 1
[0037] Take 10.5g of garbage bottom ash and 24.5g of slag into a cup, stir at 200rpm for 2min to evenly mix to obtain a solid waste mixture. Weigh 1.2310g of NaOH, 11.0555g of water glass and 10.1135g of water to evenly mix to obtain an alkaline activator. Weigh 2.8700g of tetraethylene pentamine. Add the alkaline activator and tetraethylene pentamine together to the solid waste mixture, stir at 600rpm for 20min to evenly mix, and the resulting slurry is cured at room temperature for 2 days.
[0038] Referring to patent CN118204053A, a chemical adsorption instrument was used to perform a CO2-TPD test on 80 mg of solid waste-based polymer composite carbon dioxide adsorption and desorption material with an alkali content of 14%. The spectrum is shown in the figure below. Figure 1 As shown, desorption began at 36°C and reached a peak at 171°C. The desorption peak area was 375520.6, representing an actual adsorption amount of 1.953 mmol / g.
[0039] Example 2
[0040] Take 10.5g of garbage bottom ash and 24.5g of slag into a cup, stir at 200rpm for 2min to evenly mix to obtain a solid waste mixture. Weigh 1.4068g of NaOH, 12.6348g of water glass and 9.0584g of water to evenly mix to obtain an alkaline activator. Weigh 2.9050g of tetraethylene pentamine. Add the alkaline activator and tetraethylene pentamine together to the solid waste mixture, stir at 600rpm for 20min to evenly mix, and the resulting slurry is cured at room temperature for 2 days.
[0041] Referring to patent CN118204053A, a chemical adsorption instrument was used to perform a CO2-TPD test on 80 mg of solid waste-based polymer composite carbon dioxide adsorption and desorption material with an alkali content of 16%. The spectrum is shown in the figure below. Figure 2 As shown, desorption began at 37°C and reached a peak at 179°C. The desorption peak area was 345696.5, representing an actual adsorption amount of 1.798 mmol / g.
[0042] Example 3
[0043] 10.5 g of garbage bottom ash and 24.5 g of slag were put into a cup, stirred at 200 rpm for 2 min to uniformly mix to obtain a solid waste mixture. 1.5827 g of NaOH, 14.2142 g of water glass and 8.0031 g of water were weighed and uniformly mixed to obtain an alkaline activator. 2.9400 g of tetraethylene pentamine were weighed. The alkaline activator and tetraethylene pentamine were added to the solid waste mixture together, stirred at 600 rpm for 20 min to uniformly mix, and the resulting slurry was cured at room temperature for 2 days.
[0044] The CO2-TPD test of the chemical adsorption instrument of patent CN118204053A on 80mg solid waste-based polymer composite carbon dioxide adsorption and desorption material with 18% alkali content is shown in the spectrum. Figure 3 As shown, desorption begins at 34°C and reaches a peak at 425°C. The desorption peak area is 471036.001, representing an actual adsorption amount of 2.450 mmol / g.
[0045] Example 4
[0046] Take 10.5g of garbage bottom ash and 24.5g of slag into a cup, stir at 200rpm for 2min to evenly mix to obtain a solid waste mixture. Weigh 1.7585g of NaOH, 15.7935g of water glass and 6.9480g of water to evenly mix to obtain an alkaline activator. Weigh 2.9750g of tetraethylene pentamine. Add the alkaline activator and tetraethylene pentamine together to the solid waste mixture, stir at 600rpm for 20min to evenly mix, and the resulting slurry is cured at room temperature for 2 days.
[0047] Referring to patent CN118204053A, a chemical adsorption instrument was used to perform a CO2-TPD test on 80 mg of solid waste-based polymer composite carbon dioxide adsorption and desorption material with an alkali content of 20%. The spectrum is shown in the figure below. Figure 4 As shown, desorption began at 37°C and reached a peak at 396°C. The desorption peak area was 422733.201, representing an actual adsorption amount of 2.199 mmol / g.
[0048] Example 5
[0049] 10.5 g of fly ash and 24.5 g of slag were put into a cup, stirred at 200 rpm for 2 min to uniformly mix to obtain a solid waste mixture. 2.3037 g of NaOH, 12.0415 g of water glass and 9.4548 g of water were weighed and uniformly mixed to obtain an alkali activator. 2.9400 g of tetraethylene pentamine was weighed. The alkali activator and tetraethylene pentamine were added to the solid waste mixture together, stirred at 600 rpm for 20 min to uniformly mix, and the resulting slurry was cured at room temperature for 2 days.
[0050] Referring to patent CN118204053A, a CO2-TPD test was conducted on 80 mg of solid waste, which was fly ash and slag, using a chemical adsorption instrument. The spectrum is shown in the figure below. Figure 5 As shown, desorption begins at 35°C and reaches a peak at 192°C. The desorption peak area is 511881.301, representing an actual adsorption amount of 2.663 mmol / g.
[0051] like Figure 6As shown, there is a bar chart of the CO2 adsorption capacity (adsorption at 40°C at normal pressure for 2 hours) of the solid waste-based polymer composite carbon dioxide adsorption and desorption materials prepared in Examples 1-5 of the present invention; wherein, the actual adsorption capacity of Example 1 is 1.953 mmol / g, the actual adsorption capacity of Example 2 is 1.798 mmol / g, the actual adsorption capacity of Example 3 is 2.450 mmol / g, the actual adsorption capacity of Example 4 is 2.199 mmol / g, and the actual adsorption capacity of Example 5 is 2.663 mmol / g.
[0052] Comparative Example 1
[0053] Take 10.5g of garbage bottom ash and 24.5g of slag into a cup, stir at 200rpm for 2min to evenly mix to obtain a solid waste mixture. Weigh 1.5827g of NaOH, 14.2142g of water glass and 8.0031g of water to evenly mix to obtain an alkaline activator. Weigh 2.9400g of polyethyleneimine. Add the alkaline activator and polyethyleneimine to the solid waste mixture, stir at 600rpm, and add 1.5827g of NaOH, 14.2142g of water glass and 8.0031g of water to evenly mix to obtain an alkaline activator. Figure 7 As shown, during the stirring process, polyethyleneimine will stick to the wall of the cup due to its physical properties of being too viscous and not easily soluble in water, and uneven reaction is likely to occur during synthesis, so it is not adopted.
[0054] In summary, the composite adsorption material of the present invention uses fly ash or solid waste such as waste incineration bottom ash, slag, etc. as a substrate, organic amine tetraethylenepentamine as an additive, sodium hydroxide and water glass as activators, and is prepared by a one-step reaction in an aqueous solution at normal temperature and pressure. The preparation process of the adsorption material of the present invention is simple, low in cost, and has excellent adsorption performance; the adsorption material can desorb carbon dioxide after the temperature is increased under normal pressure conditions; it not only realizes the resource disposal of solid waste, but also can adsorb and store carbon dioxide, and can also desorb carbon dioxide to extinguish fire after a fire occurs, and has good application prospects.
Claims
1. A method for preparing a solid waste-based polymer composite adsorption material, characterized in that: The solid waste-based polymer composite adsorption material has a carbon dioxide adsorption-desorption function, the solid waste is a solid waste mixture formed by mixing slag with garbage bottom ash or fly ash, and the preparation method comprises the following steps: Step 1, weighing garbage bottom ash or fly ash, slag, water glass, sodium hydroxide, water and tetraethylene pentamine in parts by weight, mixing the garbage bottom ash or fly ash and slag in a mass ratio to obtain a solid waste mixture; mixing water glass, sodium hydroxide and water to obtain an alkaline activator; Step 2, mixing the solid waste mixture, alkaline activator and tetraethylenepentamine, stirring evenly to obtain slurry, and curing at 20-35° C. to obtain a solid waste-based polymer composite adsorption material.
2. The method for preparing the solid waste-based polymer composite adsorption material according to claim 1, characterized in that: In step 1, the mass ratio of bottom ash or fly ash to slag in the solid waste is 9:1-1:
9.
3. The method for preparing the solid waste-based polymer composite adsorption material according to claim 1, characterized in that: The particle size of the garbage bottom ash and slag in step 1 is 120 mesh.
4. The method for preparing the solid waste-based polymer composite adsorption material according to claim 1, characterized in that: The particle size of the fly ash in step 1 is less than 325 mesh.
5. The method for preparing the solid waste-based polymer composite adsorption material according to claim 1, characterized in that: In step 2, the alkaline activator is calculated based on the mass percentage of Na2O in the solid waste mixture, the alkali content is 14%-20%, the water glass modulus is 0.7-1.7, and the mass ratio of water to the solid waste mixture is 0.5-0.6:
1.
6. The method for preparing the solid waste-based polymer composite adsorption material according to claim 1, characterized in that: In step 2, the loading amount of tetraethylenepentamine is 2.5wt%-10wt%.
7. The method for preparing the solid waste-based polymer composite adsorption material according to claim 1, characterized in that: In step 2, the stirring speed is 600 rpm, the stirring time is 20 minutes, and the standing time after stirring is 2 days.
8. Use of the solid waste-based polymer composite adsorption material prepared by the preparation method according to claim 1 in the adsorption and desorption of carbon dioxide.
Citation Information
Cited By
Composite adsorbent for capturing carbon dioxide as well as preparation method and application of composite adsorbent
CN120479373A